Radiation-associated angiosarcoma after breast cancer: a case report and literature review - Ostapenko, Valerijus; Ostapenko, Andrejus; Petroška, Donatas; Ostapenko, Edvinas (Lietuvos chirurgija, 2016)
IntroductionAngiosarcoma after breast cancer conservative treatment is extremely rare pathology and its early diagnostic is complicated. Due to rarity of this patology, there is still no standard approach for treatment. The aim of this article is to present a clinical case of radiation-associated angiosarcoma (RAAS) after breast cancer conservative treatment and review the latest literature sources.Case reportThis case report presents 66-year-old white postmenopausal women diagnosed with left breast cancer stage I (pT1cN0M0). Breast preserving operation was performed and patient received adjuvant radiotherapy (50 Gy). After 5 years of the follow-up, RAAS of the irradiated left breast was diagnosed. The clinical features of this rare occurrence of RAAS are presented and possible treatment options are discussed. Treatment of patient was performed in National Cancer Institute.ConclussionsEarly diagnostic, multidisciplinary approach, aggressive R0 surgical treatment and additional doses of radiotherapy – allows us to more successfully treat this rare pathological state. Scientific trials to delineate proper indications for RAAS treatment of the breast are needed.
Keywords: angiosarcoma; breast cancer; radiation-associated breast angiosarcoma